How to fall into a new routine: factors influencing the implementation of an admission and discharge programme in hospitals and general practices - Forstner, Johanna; Litke, Nicola; Weis, Aline; Straßner, Cornelia; Szecsenyi, Joachim; Wensing, Michel (BMC health services research, 2022)
The VESPEERA programme is a multifaceted programme to enhance information transfer between general practice and hospital across the process of hospital admission, stay and discharge. It was implemented in 7 hospitals and 72 general practices in Southern Germany. Uptake was heterogeneous and overall low. A process evaluation aimed at identifying factors associated with the implementation of the VESPEERA programme.